1999
DOI: 10.1046/j.1365-294x.1999.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of polyploidy and the geographic structure ofHeuchera grossulariifolia

Abstract: Multiple origins of polyploidy from an ancestral diploid plant species were investigated using restriction site polymorphism and sequence variation in the chloroplast DNA (cpDNA) of Heuchera grossulariifolia (Saxifragaceae). Phylogenetic analysis indicated that autopolyploidy has arisen at least twice in the evolutionary history of this species and potentially up to as many as seven times. These results suggest a greater range of independent polyploid origins as compared to a previous study of H. grossulariifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 65 publications
(104 reference statements)
6
125
0
1
Order By: Relevance
“…Van Dijk and BakxSchotman (1997) on Plantago media; Segraves et al (1999) on Heuchera grossulariifolia] have shown that autopolyploid taxa can arise recurrently. In general, recurrent autopolyploidization is thought to be a common phenomenon (Ramsey and Schemske 1998).…”
Section: Patterns Of Introgressive Gene Flowmentioning
confidence: 99%
“…Van Dijk and BakxSchotman (1997) on Plantago media; Segraves et al (1999) on Heuchera grossulariifolia] have shown that autopolyploid taxa can arise recurrently. In general, recurrent autopolyploidization is thought to be a common phenomenon (Ramsey and Schemske 1998).…”
Section: Patterns Of Introgressive Gene Flowmentioning
confidence: 99%
“…Most of these studies, however, involve only a single marker, often chloroplast DNA (cpDNA), and thus leave open the question of whether gene exchange and subsequent lineage recombination occurs among polyploids having different origins. Relatively few studies of wild plants (5,6) have documented both multiple origins of a polyploid species and gene flow among its genetically distinct populations. Thus, it is not known whether most wild allopolyploid species exist in nature as single gene pools or, instead, as a set of isolated populations unlinked by gene exchange.…”
mentioning
confidence: 99%
“…Although there is ample genetic evidence of multiple origins across a variety of allopolyploid taxa (e.g. Wyatt et al 1988;Ashton and Abbott 1992;Franzke and Mummenhoff 1999;Segraves et al 1999;Soltis et al 2004;Beck et al 2012;Mavrodiev et al 2015;Servick et al 2015;Vallejo-Marín et al 2015), fewer studies have experimentally compared the interfertility of independently originated populations. For instance, Modliszewski and Willis (2012) investigated the interfertility of populations of independent origin of the allotetraploid Mimulus sookensis (2n = 4x = 56), which is the polyploid derivative of hybrids between M. guttatus and M. nasutus (2n = 28) (Benedict et al 2012).…”
Section: Interfertility Of Mimulus Peregrinus Of Independent Originmentioning
confidence: 99%
“…Wyatt et al 1988;Soltis and Soltis 1991;Ashton and Abbott 1992;Doyle et al 1999;Segraves et al 1999;Beck et al 2012;Modliszewski and Willis 2012;Sampson and Byrne 2012;Mavrodiev et al 2015;Servick et al 2015;Vallejo-Marín et al 2015). Although each instance of polyploid formation may result in limited genetic diversity, mating between independently generated polyploids may introduce genetic variation into the nascent lineage and create new genetic combinations .…”
Section: Introductionmentioning
confidence: 99%